Efeito da redução do sódio do dialisato na pressão arterial de pacientes em hemodiálise - Coelho, Raissa da Mota (2011)
Effect of dialysate sodium reduction on blood pressure in hemodialysis patients, Coelho, R. M., Aracaju, 2011. Most hemodialysis patients have systemic hypertension and blood pressure levels are not controlled. One factor that may contribute to elevate blood pressure in hemodialysis patients is the increased concentration of sodium in the dialysate. Unlike the blood pressure measured in pre and post-hemodialysis, the ambulatory blood pressure monitoring is a reproducible method and includes the entire interdialytic period. A randomized cross-over trial was performed to evaluate the low sodium prescription of through a 44-hour ambulatory blood pressure monitoring in 18 patients in hemodialysis with uncontrolled hypertension who complete all phases of the study. Patients were submitted to two periods of four weeks with different sodium prescriptions separated by an equal period of interval. The sodium prescription of the standard period was 138 mEq/L and low sodium prescription was 134 mEq/L. This value was set to the mean of the pre- hemodialysis serum sodium levels by decreasing of 4 mEq/L using a direct electrode ion selective method. In the period of prescription of low sodium there was significantly sodium post-hemodialysis decreasing (138.1 + 2.0 mEq/L to 133.3 + 2.5 mEq/L, p <0.001). The average of systolic blood pressure decrease from 151.5 + 16.3 mmHg to 141.7 + 13.3 mmHg and diastolic from 99.0 + 11.0 mmHg to 92.3 + 10.2 mmHg in 44 hours and awake, but there was no reduction in diastolic blood pressure during sleep. Pulse pressure and nocturnal dipping were not altered by the intervention as well as the blood pressure measurements before and after hemodialysis, interdialytic weight gain and ultrafiltration. There was a decrease in systolic and diastolic blood pressure only in the sleep period when compared the standard and low sodium on the first interdialytic day. The trial suggests that a low sodium prescription decreased the blood pressure, assessed by ambulatory blood pressure monitoring, in hemodialysis patients with uncontrolled hypertension.